NON-DESTRUCTIVE TESTING OF THE PARTS MANUFACTURED BY DIRECT METAL LASER SINTERING - Kouprianoff, D.; du Plessis, A.; Yadroitsava, I.; Yadroitsev, I. (SUNConferences, 17th Annual Conference of the Rapid Product Development Association of South Africa, 2016)
Interest in Additive Manufacturing (AM) has grown considerably in the past decades. The industry has gained the great benefits from this type of technologies. The main advantages being geometrical freedom that allows designing parts with complex shape, which are difficult or impossible to produce by conventional technology, shortened design to product time, customization and possible use of several materials in one process. Direct Metal Laser Sintering (DMLS) is one of the most promising AM techniques that utilize metal materials. Due to the complex nature of the DMLS process, one of the drawbacks is the high residual stress in the manufactured parts. This can result to the formation of internal cracks and eventually to a substantial deterioration of the mechanical properties of the products and their application properties. For this reason it is very important to identify defective parts before enrolling into service. Non-destructive testing (NDT) is effective for detection of internal defects without causing damage. NDT also covers a wide group of methods of analysis used to evaluate the properties of a material. NDT techniques like ultrasonic inspection, acoustic emission, visual inspection, thermography, X-ray and 3D computed tomography (CT) inspection, etc. are now widely used for various industrial applications. For the detection of defects and to study the properties of the material each of these methods uses different physical principles that have their advantages and disadvantages. In this study some of the NDT techniques in terms of their applicability to the inspection of parts manufactured by DMLS technology are considered.
Published Conference Proceedings
Keywords: Additive manufacturing; Non-destructive testing; Direct Metal Laser Sintering; CT scans